HIDDEN MOTIVES BEHIND THE WHITE’S DEFENCE TOWARDS THE BLACK IN GRISHAM’S A TIME TO KILL - Sriastuti, Anna (Language Circle: Journal of Language and Literature, 2015)
The purpose of this study is to reveal the hidden motives of the White behind race and class struggles in Carl Lee‘s case of murdering two local young white men who had raped his 10 years old daughter, Tonya, and left her bruised and bloodied. Lee, a black man, who used to have good relations with the White stood against the White at the court when he decided to kill the rapists in his own hands as his revenge to his daughter. The story was not simply telling readers about the races and classes struggles between the Black and the White but another important point to notice was the wilingness of some white people who posted themselves in Lee‘s side that led further conflict of the White against the White.